2009
DOI: 10.1002/dvdy.22015
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin‐11 controls otolith assembly: Evidence for extracellular cadherin activity

Abstract: Cadherin-11/Cdh11 is expressed through early development and strongly during inner ear development (otic placode and vesicle). Here we show that antisense knockdown of Cdh11 during early zebrafish development interferes with otolith formation. Immunofluorescence labeling showed that Cdh11 expression was concentrated on and within the otolith. Cdh11 was faintly detected at the lateral surface (sites of cell-cell contact) of otic epithelial cells and in the cytoplasm. Strongly labeled Cdh11 containing puncta wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Electron microscopy and time-lapse analyses show that otolith growth starts as a nucleus of spherules aggregating at the top of a tether cilium (Fig. 3F) (Pisam et al, 2002) and suggest that otoliths form through spherule self-aggregation (Clendenon et al, 2009). Spherules are secreted from the apical regions of the epithelial cells that line the inner ear cavity (Riley et al, 1997;Pisam et al, 2002) (Fig.…”
Section: Rotational Flow and Mixing In Vivo: Zebrafish Otolithic Biommentioning
confidence: 98%
“…Electron microscopy and time-lapse analyses show that otolith growth starts as a nucleus of spherules aggregating at the top of a tether cilium (Fig. 3F) (Pisam et al, 2002) and suggest that otoliths form through spherule self-aggregation (Clendenon et al, 2009). Spherules are secreted from the apical regions of the epithelial cells that line the inner ear cavity (Riley et al, 1997;Pisam et al, 2002) (Fig.…”
Section: Rotational Flow and Mixing In Vivo: Zebrafish Otolithic Biommentioning
confidence: 98%
“…The otic cavity contains precursor 1–3 micron particles, or spherules, secreted from the apical portions of the epithelial cells of the inner ear (Riley et al, 1997). Time lapse analysis and electron microscopy show that otolith growth starts as a nucleus of spherules aggregating at the top of a tether cilium (Clendenon et al, 2009; Pisam et al, 2002). At 30hpf, a mineralized ovoid otolith is visible (Pisam et al, 2002; Sollner et al, 2003) and concentric arrays of spherule deposition are seen at the periphery of the nascent otolith (Pisam et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…CDH23 (Bork et al 2001) and PCDH15 (Ahmed et al 2003)) and facilitates cell–cell adhesion and signaling in various tissues. The Cadherin 11 gene ( CDH11 ; MIM 600023) was shown to be necessary for otolith assembly in the developing zebra fish embryo (Clendenon et al 2009) and was also reported to be expressed in the human fetal cochlea (Skvorak et al 1999). The Cadherin 1 ( CDH1 ; MIM 192090) localizes to the apical intercellular junctions of supporting cells within the murine organ of Corti suggesting a role in inter-supporting cell adhesion (Whitlon 1993).…”
Section: Discussionmentioning
confidence: 99%